2009
DOI: 10.4102/ojvr.v76i2.45
|View full text |Cite
|
Sign up to set email alerts
|

The comparative prevalence of five ixodid tick species infesting cattle and goats in Maputo Province, Mozambique

Abstract: This study compares the prevalence of ixodid tick species on cattle and goats in Maputo Province. Adult ticks as well as the nymphs of three species, and only the adults of two species were collected from sets of five cattle at 21 localities throughout the province and compared with those collected from similar sets of goats at the same places. Amblyomma hebraeum adults and/or nymphs were present on cattle and on goats at all 21 localities, and 90 cattle and 22 goats were infested with adult ticks. Rhipicephal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…Domestic cattle are the most efficient hosts of R. microplus (Mason and Norval 1980). Goats play a lesser, but still significant role (Nyangiwe and Horak 2007;De Matos et al 2009), and as demonstrated on the farms 'Pumprock' and 'Shweme' in this study. It is thus on cattle and possibly to a lesser extent on goats, purchased in localities 13 13 where R. microplus is present, that it has been introduced into the region.…”
Section: Discussionsupporting
confidence: 52%
“…Domestic cattle are the most efficient hosts of R. microplus (Mason and Norval 1980). Goats play a lesser, but still significant role (Nyangiwe and Horak 2007;De Matos et al 2009), and as demonstrated on the farms 'Pumprock' and 'Shweme' in this study. It is thus on cattle and possibly to a lesser extent on goats, purchased in localities 13 13 where R. microplus is present, that it has been introduced into the region.…”
Section: Discussionsupporting
confidence: 52%
“…By comparison, R. microplus seems to prefer the coastal regions of the country, displaying a discontinuous distribution in the more temperate regions [5][6][7]. Recent studies documented the adaptive ability of R. microplus ticks as they move into previously unsuitable environments to displace the native R. decoloratus tick species [8][9][10]. The spread of R. microplus to previously unoccupied areas is of great economic concern, since South African cattle are immunologically naïve to B. bovis [1].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have focused on the relationship that exists between this sub-group of the Rhipicephalus species and results have indicated that Rhipicephalus microplus is displacing other ticks of the same genus in West Africa, South Africa, Tanzania, Mozambique and more recently also in Namibia (De Clercq et al, 2012;De Matos et al, 2009;Lynen et al, 2008;Nyangiwe et al, 2013a;Nyangiwe et al, 2013b). In Zimbabwe, Mason and Norval (1980) reported that the exotic R. microplus was displacing the autochthonous Rhipicephalus decoloratus in the eastern parts of the country with unconfirmed reports suggesting that because of the 1980-1983 drought R. microplus could actually have disappeared from the country (Norval et al, 1992), while subsequent research revealed that R. microplus was still limited to the eastern and northern parts of the country (Katsande et al, 1996) and that it could periodically spread into the interior areas of Zimbabwe (Smeenk et al, 2000).…”
Section: Introductionmentioning
confidence: 99%